The Development of Mushroom Interactive Student Worksheet Based on Discovery Learning as Teaching Materials for Class X High School Students (FMIPA UNNES, 2023)
The 2013 curriculum requires students to understand various subject matter actively and independently. One of the materials that make it difficult for students to learn is the mushroom material. For this reason, it is necessary to apply a discovery learning model to mushroom material. In addition, the process of learning biology at SMA N 1 Kebumen has not yet utilized technology optimally. The LKPD used is still in printed form and is sourced from textbooks only. So we need an interactive electronic LKPD with varied learning resources. The purpose of this study was to analyze the validity and effectiveness of interactive teaching materials. The research method, namely Research and Development, uses steps to a small scale. The subjects in this study were 15 students taken using the